Electrocardiographic abnormalities associated with raised intracranial pressure. Issue 5952 (1st February 1975) - Jachuck, S J; Ramani, P S; Clark, F; Kalbag, R M
Abstract : Serial electrocardiographic (E.C.G.) recordings were taken in seven patients suffering from intracranial conditions, for which their intracranial pressure was directly and continuously monitored with a Konigsberg extradural transducer. The E.C.G. changes observed in patients with raised intracranial pressure were prominent U waves, ST-T segment changes, notched T waves, and shortening and prolongation of Q-T intervals. Two patients with normal intracranial pressure showed no E.C.G. abnormalities but also establish a relationship between E.C.G. abnormalities and changing intracranial pressure.